Tender Conspiracy In Electronic Procurement Of Goods And Services (A Study Of Case Number 04/KPPU-L/2015) - Wibowo, Sigit (Prophetic Law Review, 2021)
This research studied and analyzed why there is still tender conspiracy on government projects and construction work contracts through the e-procurement system. This was a normative legal research which analyzed principles, norms, propositions of applicable regulations, described existing phenomena, and analyzed them systematically. Using a statute approach and a case approach related to the implementation of the laws and regulations concerning electronic procurement services (e-procurement) in a construction service work contract in government projects according to the positive law of the Republic of Indonesia. It is necessary to immediately enact laws and regulations which cover a wider scope in terms of procurement and strengthen law enforcement in relation to the procurement of goods and/or services by the government. It is intended to minimize abuse of power/authority of tender committee, business players, and tender participants to prevent unfair competition, where conspiracy still takes place in government project tender.Keywords: Tender Conspiracy; Electronic Procurement of Goods and Services; Case Number 04/KPPU-L/2015Konspirasi Tender Dalam Pengadaan Barang Dan Jasa Elektronik (Studi Kasus Nomor Perkara 04/Kppu-L/2015)AbstrakPenelitian ini mengkaji dan menganalisis mengapa masih terjadi persekongkolan tender proyek pemerintah dan kontrak karya konstruksi melalui sistem e-procurement. Penelitian ini merupakan penelitian hukum normatif yang menganalisis asas, norma, dalil peraturan yang berlaku, mendeskripsikan fenomena yang ada, dan menganalisisnya secara sistematis. Menggunakan pendekatan undang-undang dan pendekatan kasus terkait dengan pelaksanaan peraturan perundang-undangan tentang jasa pengadaan secara elektronik (e-procurement) dalam suatu kontrak karya jasa konstruksi pada proyek-proyek pemerintah menurut hukum positif Negara Kesatuan Republik Indonesia. Peraturan perundang-undangan yang cakupannya lebih luas dalam hal pengadaan dan penguatan penegakan hukum terkait pengadaan barang dan/atau jasa oleh pemerintah perlu segera ditetapkan. Hal ini dimaksudkan untuk meminimalisir penyalahgunaan wewenang/wewenang panitia lelang, pelaku usaha, dan peserta lelang untuk mencegah terjadinya persaingan tidak sehat, dimana masih terjadi persekongkolan dalam tender proyek pemerintah.Kata kunci: Konspirasi Tender; Pengadaan Barang dan Jasa Secara Elektronik; Nomor Perkara 04/KPPU-L/2015